Synthesis and Some Reaction of 2-[α-Benzoylaminostyryl]-6, 8-Dibromo-3,1-Benzoxazin-4(H)-one, Quinazolin-4(3H)-one and Chloroquinazoline Derivatives with Some Nucleophilic Reagents - EL-Nagdy, S. (Asian Journal of Chemistry, 2010)
2-[α-Benzoylamino-p-chlorostyryl]-6, 8-dibromo-3, 1-benzoxazine-4(H)-one (II) has been prepared from N-[α-benzoylamino-p-chlorocinnamoyl]-3, 5-dibromoanthranilic acid (I). The benzoxazinone (II) was found to undergo ring opening reaction with different nitrogen nucleophiles to give (III). Similarly with secondary amines and hydrazines to give (IV) and (V). Reaction of (Va) with different aldehydes and acetylation gave bases (VI) and (VII) respectively. (II) reacted with hydrazoic acid to give the Schiff's benzimidazole derivative (VIII) beside the tetrazole derivative (IX). (II) also reacted with aromatic hydrocarbons under Friedel-Craft's conditions to give (X). (II) reacted with ethyl acetoacetate, as a carbon nucleophile, and maleic anhydride to give (XI) and (XII) respectively. Fusion of (II) with ammonium acetate gave the quinazolinone (XIII), while (XIII) condensed with formaldehyde in the presence of succinimide and/or benzamide to give Mannich bases (XIV); furthermore, alkylation of (XIII) with sodium ethoxide and methyl iodide gave (XIX) and (XX) respectively. On the other hand, chlorination of (XIII) with a mixture of POCl3/PCl5 gave (XVII); fusion of (XVII) with anthranilic acid gave (XVIII); also (XVII) reacted with both thiourea and hydrazoic acid to give (XIX) and (XX) respectively. Also (II) has been transformed to the thione (XXI) by the action of P2S5.